PERANAN GURU DALAM MENGENALKAN PENDIDIKAN SEKS PADA ANAK DI TAMAN KANAK-KANAK PERTIWI - Oktavianti, Mira; Fadillah, Fadillah; Purwanti, Purwanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Â AbstractThis study aims to describe the role of teachers in introducing sex education to children in TK Pertiwi, West Pontianak. The method used is descriptive method with a qualitative approach. Data collection techniques are in the form of interview techniques, direct observation techniques and documentation techniques. The research subjects were B3 class teachers and children aged 5-6 years in B3 class at TK Pertiwi 1 Pontianak Barat. Data analysis techniques are analysis techniques of data collection, data reduction, data presentation and conclusion drawing. From the data analysis, the researchers found that the teacher had taught and introduced sex education correctly to the children of TK Pertiwi 1 Pontianak Barat. The role of the teacher in planning learning by the way the teacher prepares and makes the RKH in accordance with the level of development of the child, the teacher in carrying out learning by introducing the names of body members, functions of the body members and how to care for the limb The teacher introduces excellent sex education to children.Keywords : Role Teacher, Sex Education, Early Childhood